2018
DOI: 10.1016/j.apcatb.2018.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Co4N/nitrogen-doped graphene: A non-noble metal oxygen reduction electrocatalyst for alkaline fuel cells

Abstract: Cobalt-nitride (Co 4 N) nanoparticle-decorated nitrogen-doped graphene sheets were obtained via the nitrogen doping of a graphene-oxide precursor and simultaneous nitride formation. The non-precious metal catalyst formed in this one-step synthesis exhibits high electrocatalytic oxygen reduction activity and hence provides a promising alternative to conventional Pt/C alkaline fuel cell cathode catalysts. The reported composites were formed from the mixture of lyophilized graphene-oxide nanosheets and cobalt(II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(30 citation statements)
references
References 72 publications
1
27
0
2
Order By: Relevance
“…25. There are two peaks located at 682 and 520 cm −1 for our pristine PW-Co 3 N NWA/NF, which is consistent with previous reports 30,55,56 . When the applied potential increased till 0.8 V vs. RHE, the peaks of PW-Co 3 N NWA/NF remained constant, which implied that there was no visible surface change during the HzOR process within the measured potential range.…”
Section: Discussionsupporting
confidence: 93%
“…25. There are two peaks located at 682 and 520 cm −1 for our pristine PW-Co 3 N NWA/NF, which is consistent with previous reports 30,55,56 . When the applied potential increased till 0.8 V vs. RHE, the peaks of PW-Co 3 N NWA/NF remained constant, which implied that there was no visible surface change during the HzOR process within the measured potential range.…”
Section: Discussionsupporting
confidence: 93%
“…Two peaks at approximately 1342.0 and 1585.0 cm −1 , representing the defects and disordered carbon (D-band) and sp 2 graphitic carbon (G-band), respectively, can be observed in Co@CoSA/N-CNT/CC and Co 4 N@CoSA/N-CNT/CC. Three additional weak Raman peaks are detected at 468.4, 509.7, and 672.9 cm −1 in Co 4 N/CC and Co 4 N@CoSA/N-CNT/CC, which can be attributed to the meaningful contribution of the cobalt nitride phase 23 . Interestingly, the intensities of the D band to G band (I D / I G ) of Co 4 N@CoSA/N-CNT/CC are calculated to be 1.11, which is higher than the value of 0.96 for Co@CoSA/N-CNT/CC.…”
Section: Resultsmentioning
confidence: 94%
“…This speculation was supported by the XPS result of the post‐used Pd/Co 3 N‐Ni 3 N/CFC catalyst. It was found that the O 1s spectra of the spent catalyst can be deconvoluted well into three characteristic peaks at 530.7, 531.8, and 533.4 eV, which correspond to the nickel/cobalt oxides, carboxyls, and hydroxys, respectively (Figure S3, Supporting Information) 55–57. In addition, CO stripping experiments further provided evidence supporting the promoting effect of synergistic phases in oxidative removal of carbonaceous intermediates.…”
Section: Resultsmentioning
confidence: 75%